2004
DOI: 10.1158/1078-0432.ccr-04-1200
|View full text |Cite
|
Sign up to set email alerts
|

S-1 Plus Cisplatin Combination Chemotherapy in Patients with Advanced Non–Small Cell Lung Cancer

Abstract: Purpose: To evaluate the efficacy and toxicity of a novel combination chemotherapeutic regimen including cisplatin with an oral anticancer agent, S-1 that consisted of tegafur, 5-chloro-2, 4-dihydroxypyridine, and potassium oxonate, for non-small-cell lung cancer (NSCLC) patients.Experimental Design: In this phase II trial, patients with locally advanced and metastatic NSCLC were treated with the oral administration of S-1 at 40 mg/m 2 twice a day for 21 consecutive days while cisplatin (60 mg/m 2 ) was admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 24 publications
3
73
1
Order By: Relevance
“…Therefore, it is important to inhibit the DPD activity to improve the responsiveness to 5-FU against DPD-positive NSCLCs. Recently, S-1 (a combination of tegafur, gimeracil, and oteracil potassium, Taiho) has been developed for clinical use (Chu et al, 2004;Ichinose et al, 2004). Gimeracil used in S-1 is a stronger inhibitor for the intratumoural DPD activity than uracil used in UFT.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to inhibit the DPD activity to improve the responsiveness to 5-FU against DPD-positive NSCLCs. Recently, S-1 (a combination of tegafur, gimeracil, and oteracil potassium, Taiho) has been developed for clinical use (Chu et al, 2004;Ichinose et al, 2004). Gimeracil used in S-1 is a stronger inhibitor for the intratumoural DPD activity than uracil used in UFT.…”
Section: Discussionmentioning
confidence: 99%
“…Tegafur, a prodrug of 5-fluorouracil (5-FU), is gradually converted to 5-FU, and is rapidly catabolized by dihydropyrimidine dehydrogenase in the liver. In several studies, S-1 has been reported to actively reduce tumor growth in various human cancers, and a combination of platinum-based regimens with S-1 has been the standard treatment regimen against advanced NSCLC (7)(8)(9)(10)(11)(12). Gemcitabine, an anticancer drug that structurally resembles cytosine arabinoside, has been demonstrated to exhibit high anti-tumor activity with minimal adverse effects (13).…”
Section: Introductionmentioning
confidence: 99%
“…The phase II and phase III trials of S-1 plus platinum documented that S-1 is effective against both adenocarcinoma (ADC) and squamous cell carcinoma (SQCC), suggesting that S-1 is a valid treatment option. 6,7 EGFR mutation status is well known as a predictor of response to treatment by EGFR tyrosine kinase inhibitor (EGFR-TKI) and as the target of EGFR-TKIs. [8][9][10] In 2007, Suehisa and colleagues reported that adjuvant chemotherapy with uraciltegafur significantly prolonged survival rates among patients with EGFR wild-type adenocarcinoma but not among patients with EGFR mutant tumors.…”
Section: Introductionmentioning
confidence: 99%